(untitled) (Global Conference on Medical and Health Sciences, 2026)
The menisci of the knee joint are fibrocartilaginous structures of critical functional importance, providing load distribution, shock absorption, joint stabilisation, and lubrication across the tibiofemoral articulation (Makris et al., 2011; Fox et al., 2015). Composed predominantly of type I collagen arranged in circumferential and radial fibre bundles, with a sparse population of fibrochondrocytes embedded in a proteoglycan-rich extracellular matrix, the menisci are capable of transmitting up to 50–70% of the compressive load in the knee joint during weight-bearing activities (Englund et al., 2009; Berthiaume et al., 2005).